The impact of the European Association of Endoscopic Surgery research grant scheme—a mixed qualitative quantitative methodology study protocol - McClean, Adam; Huo, Bright; Kwan, Jing Yi; Long, Judith; Walshaw, Josephine; Mesri, Mina; Francis, Nader; Arulampalam, Tan H.; Chetter, Ian; Yiasemidou, Marina (Frontiers in Surgery, 2023)
Background The European Association of Endoscopic Surgery (EAES) is a surgical society who promotes the development and expansion of minimally invasive surgery to surgeons and surgical trainees. It does so through its activities in education, training, and research. The EAES research committee aims to promote the highest quality clinical research in endoscopic and minimally invasive surgery. They have provided grant funding since 2009 in education, surgery, and basic science. Despite the success and longevity of the scheme, the academic and non-academic impact of the research funding scheme has not been evaluated. Aims The primary aim of this project is to assess the short, long term academic and real world impact of the EAES funding scheme. The secondary aims are to identify barriers and facilitators for achieving good impact. Methods This will be a mixed qualitative and quantitative study. Semi-structured interviews will be performed with previous grant recipients. The questions for the interviews will be selected after a consensus is achieved amongst the members of the steering committee of this project. The responses will be transcribed and thematic analysis will be applied. The results of the thematic analysis will be used to populate a questionnaire which will be disseminated to grant recipients. This study is kindly funded by the EAES. Discussion The first question this project is expected to answer is whether the EAES research funding scheme had a significant positive impact on research output, career progression but also non-academic output such as change in clinical guidelines, healthcare quality and cost-effectiveness improvement. This project however is also expected to identify facilitators and barriers to successful completion of projects and to achieving high impact. This will inform EAES and the rest of the surgical and academic communities as to how clinicians would like to be supported when conducting research. There should also be a positive and decisive change towards removing factors that hinder the timely and successful completion of projects.